Design of circularly polarized unidirectional antenna using probe-excited circular ring antenna above the square reflector with inserted metallic slabs - Phongcharoenpanich, Chuwong; Lertsakwimarn, Kittima; Sukkamat, Rungsinee; Mhudtongon, Nattaset; Kosulvit, Sompol; Akkaraekthalin, Prayoot (My University, 2017)
This paper proposes a circularly polarized unidirectional antenna using a probe excited circular ring with inserted perpendicular slabs above the square reflector for UHF-RFID system. The measured S11 ≤ -10 dB covers 884-1000 MHz or 12.31% bandwidth, and 3-dB AR bandwidth of 900-1000 MHz or 10.53% bandwidth. The maximum gain is 8.35 dBic. The half-power beamwidths in xz-and yz-planes are 66.3 and 66.7 degrees, respectively.
Keywords: Circular polarization (CP); Circular ring; UHF-RFID; Unidirectional pattern